Cathelicidin-derived antiviral peptide inhibits herpes simplex virus 1 infection - Guo, Xiaomin; An, Yanxing; Tan, Wanmin; Ma, Ling; Wang, Mingyang; Li, Juyan; Li, Binghong; Hou, Wei; Wu, Li (Frontiers in Microbiology, 2023)
Herpes simplex virus 1 (HSV-1) is a widely distributed virus. HSV-1 is a growing public health concern due to the emergence of drug-resistant strains and the current lack of a clinically specific drug for treatment. In recent years, increasing attention has been paid to the development of peptide antivirals. Natural host defense peptides which have uniquely evolved to protect the host have been reported to have antiviral properties. Cathelicidins are a family of multi-functional antimicrobial peptides found in almost all vertebrate species and play a vital role in the immune system. In this study, we demonstrated the anti-HSV-1 effect of an antiviral peptide named WL-1 derived from human cathelicidin. We found that WL-1 inhibited HSV-1 infection in epithelial and neuronal cells. Furthermore, the administration of WL-1 improved survival rate and reduced viral load and inflammation during HSV-1 infection via ocular scarification. Moreover, facial nerve dysfunction, involving the unnormal blink reflex, nose position and vibrissae movement, and pathological injury were prevented when HSV-1 ear inoculation infected mouse were treated with WL-1. Together, our findings demonstrate that WL-1 may be a potential novel antiviral agent against HSV-1 infection induced facial palsy.